问题
解答题
解方程: (1)x2-10x+25=7 (2)3x2+8x-3=0 (3)x2-2
(4)x2-8x=9 (5)
(6)(x-2)2=(2x+3)2. |
答案
(1)x2-10x+25=7,
变形为:x2-10x+25-7=0,
x2-10x+18=0,
∵a=1,b=-10,c=18,
∴x=
=-b± b2-4ac 2a
=5±10±2 7 2
,7
∴x1=5+
,x2=5-7
;7
(2)∵a=3,b=8,c=-3,
∴x=
=-b± b2-4ac 2a
=-8± 64+36 6
,-4±5 3
∴x1=-3,x2=
;1 3
(3)∵a=1,b=-2
,c=2,2
∴x=
=-b± b2-4ac 2a
=2 2 2
,2
∴x1=x2=
;2
(4)x2-8x=9,
变形为:x2-8x-9=0,
(x-9)(x+1)=0,
则:x-9=0或x+1=0,
解得:x1=9,x2=-1;
(5)方程可变形为:2y2+y-6=0,
a=2,b=1,c=-6,
∴y=
=-b± b2-4ac 2a
=-1± 1+24 4
,-1±5 4
∴y1=-
,y2=1;3 2
(6)(x-2)2=(2x+3)2.
变形为:(x-2)2-(2x+3)2=0,
(x-2+2x+3)(x-2-2x-3)=0,
(3x+1)(-x-5)=0,
则:3x+1=0,-x-5=0,
解得:x1=-
,x2=-5.1 3